Lorentz Force Experiment Prop based on IoT (E-Lorentz) to Support the Learning Process of Physics Subject for 9th Grade - Hana Rifdah Sakinah; Novian Anggis Suwastika; Muhammad Al Makky; Qori Qonita (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Lorentz force teaching aids are proven to improve student’s cognitive abilities. The average result of N-Gain after using Lorentz force prop is 0.8 which is included in the high category. In the learning process, the teacher needed to design the course content, guiding, directing, and evaluating student learning outcomes. In the current situation, this learning process is still being done conventionally. Along with the development of technology, the Internet of Things (IoT) can facilitate the teaching and learning process. IoT allows data to be sent across a network without the need for human-to-human or human-to-computer interaction. The implementation of IoT in Education can also be called Internet of Education Things (IoET). IoT has many benefits in the teaching and learning process for both teachers and students. Students can learn directly with teaching aids so that their cognitive understanding increases. Teachers can also curtail activities that were previously done manually by reading activities that have been automatically saved, such as preparing, directing, giving questions, to recapitulating assessments. In this study, IoT technology has been implemented into the Lorentz force teaching aid (E-Lorentz)  and the system performance has been analyzed based on its functionality parameters, accurate data reading and suitability of the assessment are the main parameters. The reading accuracy test yielded a difference of 0.474 X 10-4 N, with an error percentage of 2.92% determined by using the Mean Absolute Percentage Error (MAPE) method. Data reading and suitability of the assessment have been tested and are able to run efficiently at 100%